(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
High initial cost is one of the reasons why consumers think twice before investing on the conventional solar water heating systems, especially in low income countries. Integrated collector storage systems are available at a lesser cost, but with a penalty of decreased efficiency. In this paper, yet another attempt to reduce cost of solar water heating system has been made by using independent plane reflectors along with an insulated storage tank provided with a heat absorbing aperture. With no tracking arrangement, this system uses only the intense beam radiation available from 9:00 AM to 3:00 PM with a concentration factor of 10. A theoretical study was conducted using commercial computational fluid dynamics software which was followed by an experimental validation of the results. The theoretical results were in agreement with the experimental results. The efficiency of this system was less than collector storage systems reported in the literature by about 10-15%. Maximum average tank temperature of 350 K and efficiency of 0.61 was obtained. Overall loss coefficient was identical with that of existing integrated collector storage systems. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22128 Bangladesh J. Sci. Ind. Res. 49(3), 147-154, 2014